2023
DOI: 10.32604/csse.2023.022385
|View full text |Cite
|
Sign up to set email alerts
|

Skin Lesion Classification System Using Shearlets

Abstract: The main cause of skin cancer is the ultraviolet radiation of the sun. It spreads quickly to other body parts. Thus, early diagnosis is required to decrease the mortality rate due to skin cancer. In this study, an automatic system for Skin Lesion Classification (SLC) using Non-Subsampled Shearlet Transform (NSST) based energy features and Support Vector Machine (SVM) classifier is proposed. At first, the NSST is used for the decomposition of input skin lesion images with different directions like 2, 4, 8 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…To evaluate the generalization capability of SVM models, the application of crossvalidation techniques is a common practice [41,42]. Prior studies have effectively demonstrated the generalization achieved through cross-validation [43] by training SVM models on a discovery dataset and subsequently assessing their performance using a distinct replicated dataset [44]. In the approach, internal tenfold cross-validation [45] was employed to optimize model performance.…”
Section: Generalization Discussion Of the Classifiers Modelsmentioning
confidence: 99%
“…To evaluate the generalization capability of SVM models, the application of crossvalidation techniques is a common practice [41,42]. Prior studies have effectively demonstrated the generalization achieved through cross-validation [43] by training SVM models on a discovery dataset and subsequently assessing their performance using a distinct replicated dataset [44]. In the approach, internal tenfold cross-validation [45] was employed to optimize model performance.…”
Section: Generalization Discussion Of the Classifiers Modelsmentioning
confidence: 99%